2007
DOI: 10.2341/06-27
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Previous Provisional Cementation on the Bond Strength Between Two Definitive Resin-based Luting and Dentin Bonding Agents and Human Dentin

Abstract: Clinical RelevanceBased on in vitro results in extracted teeth, the dual bonding method used was effective in restoring the shear bond strength values that decreased after applying provisional luting agent regardless of the composition of the provisional luting agent (eugenol-based or eugenolfree) used. SUMMARYThis study evaluated the effect of two different types of provisional luting agents (RelyX Temp E, eugenol-based; RelyX Temp NE, eugenol-free) on the shear bond strengths between human dentin and two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 32 publications
0
34
1
2
Order By: Relevance
“…In this study the temporary material was mechanically removed using a curette [9] before cleaning with non-fluoridated pumice flour and conditioning with acid. The shear bond strength values following this cleaning were similar to those of the control group, in contrast to previous reports [3,14,17]. It is possible that the mechanical cleaning efforts are responsible for the improved bonding in general [18].…”
Section: Resultscontrasting
confidence: 53%
“…In this study the temporary material was mechanically removed using a curette [9] before cleaning with non-fluoridated pumice flour and conditioning with acid. The shear bond strength values following this cleaning were similar to those of the control group, in contrast to previous reports [3,14,17]. It is possible that the mechanical cleaning efforts are responsible for the improved bonding in general [18].…”
Section: Resultscontrasting
confidence: 53%
“…[10][11][12][13]15,[18][19][20][21][23][24] However, these studies reported conflicting results. Despite other methodological differences, the exposure period to ZOE has not been standardized during these studies, which may have affected the results.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have found that eugenol-containing cements did not reduce the bond strength to dentin. 10,12,15,[23][24] However, other studies have reported contradictory results. 11,13,[18][19][20][21] These differences in results can be explained by differences between the adhesive systems and methodologies used.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations